FIRST REPORT ON THE FEEDING BEHAVIOR OF EARLESS MONITOR, LANTHANOTUS BORNEENSIS AND ITS PREDATION ON RICE FIELD FROG, FEJERVARYA LIMNOCHARIS IN A CAPTIVE ENVIRONMENT - Ahmad Nauval Arroyyan (Treubia, 2021)
Being endemic to Borneo, the Earless monitor, Lanthanotus borneensis (Steindachner, 1878) is rarely found in its habitats due to its cryptic behavior. We provide care for confiscated animals in the Reptile House of Museum Zoologicum Bogoriense (MZB) in Cibinong, West Java, Indonesia since 2014. Little is known on its natural prey but from scattered descriptive reports. This study is aimed at documenting the feeding behavior of ten captive Earless monitors and events of predation on frogs. We set up two experiments, one with meat of Rice Field Frog, Fejervarya limnocharis, and the other with live frog of the same species. Our recorded observations ran for four weeks for the frog meat feeding experiment and followed by the frog predation experiment. Our results showed that lizards constantly accepted frog meat. Lizards tended to feed before sunset for a short period of time on the muddy soil surface, although a few individuals inconsistently fed under water. The average body mass for these lizards increased by 4.29 g and average SVL by 0.45 cm. We recorded predation on frogs in three out of ten individuals observed during this study. If F. limnocharis is confirmed to occur in the natural habitats of L. borneensis, it is possible that this frog species is among the natural prey for Earless monitors. Further studies on its natural diets should be conducted to gain in-depth knowledge essential for generating effective captive husbandry for this nationally protected species in Indonesia.